Scleral necrosis after scleral buckling surgery of the patient with pyoderma gangrenosum - Kmera-Muszyńska, Maria; Tesla, Piotr; Okruszko, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Pyoderma gangrenosum (PG) is a rare skin disease caused by immune dysfunction. The systemic diseases are often associated. The aim of the study was to report necrotic scleritis which developed after scleral buckling procedure in the case of the 64 years old patient suffered from primary retinal detachment and idiopathic PG. The retinal reattachment was achieved. The conjunctival wound dehiscence, necrotising scleritis and marginal keratitis as a manifestation of the patergic reaction were diagnosed. The treatment with corticosteroids locally (Dexamethason) and systematically (Prednison and Sulfasalazine), was administrated. The improvement and stabilisation of the local condition of ocular surface were observed. After reduction of systemic drugs, the exacerbation of local inflammation and vitritis was observed. The prolonged therapy was necessary. The risk of wound healing disturbances of an ocular surface with aggravated necrotic reaction must be expected after ocular surgery of the patient with PG. The adequate immunosupressive prolonged treatment with proper collaboration with the dermatologist is necessary.